O caminho da nossa vida, uma aproximação entre Ser e tempo e Divina comédia - Villela, Felipe Stiebler Leite (2010)
The present study intended an approach between Heidegger´s thoughts in Being and time and Dante´s poetry in Divine comedy. The approach aroused from the knowledge that both works bring a comprehension of the human existence, each one in a proper way. In order to accomplish that it was necessary a non dogmatic reading of Divine comedy, that is, a non certain reading by any religious dogmatism. This approach was organized in four main points where we found accordance in both works. That is: Care and Way ; Falling and Perdition ; Temporality and Eternity and Authenticity and Salvation . In each one of those topics it was possible from the approach between both works an amplification of Dante´s poetic images and Heidegger´s concepts. With the development of the approach, we came across that the guilt concept has a central part in Divine comedy as much as in Being and time. The approach between those works, as well as its readings, is one among many others possible. This study did not intend to be more than the beginning of a conversation between Martin Heidegger s thought and Dante Alighieri s poetry